Potential of custom freight agent department of Kuala Lumpur Airport services to become international freight forwarder / Intan Nadiya Tormudzi - Tormudzi, Intan Nadiya (Faculty of Business and Management, 2011)
This paper investigate the potential and opportunity of KLAS Custom Freight Agent department as a freight agent to become international freight forwarder in future. It consists of investigating of the important elements that CFA need to understand in order to adapt internationalization in its business. The first element is research on the opportunity and threat faced to enter into international business environment. Second is to gauge the performance and achievement of CFA in order to know whether CFA is able or may manage to become internationalize. The findings presented will focus on this main issues.